2017
DOI: 10.1007/s10484-016-9347-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Stress on Decision Making

Abstract: The study examined the effects of a social stressor (Trier Social Stress Test) on 24 male and 32 female college students’ affective and physiological reactivity and their subsequent performance on a decision-making task (Iowa Gambling Task). The 56 participants were randomly assigned to a social stressor or a control condition. Compared to controls, participants in the stress condition responded with higher heart rates and skin conductance responses, reported more negative affect, and on the decision-making ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 45 publications
5
51
0
9
Order By: Relevance
“…Acute stress has been found both to facilitate and to impair performance in a variety of contexts; however, complex cognitive processing and functions, where stressors occur peripherally to the primary task, are generally found to be impacted negatively by increased stress. This is particularly relevant to the surgical environment, where stress and stressors have been shown to adversely impact functions such as decision‐making and team performance. Studies have observed stress in the live operating theatre using a variety of methods , but limitations in ECG equipment and stress measurement methods have hindered research.…”
Section: Introductionmentioning
confidence: 99%
“…Acute stress has been found both to facilitate and to impair performance in a variety of contexts; however, complex cognitive processing and functions, where stressors occur peripherally to the primary task, are generally found to be impacted negatively by increased stress. This is particularly relevant to the surgical environment, where stress and stressors have been shown to adversely impact functions such as decision‐making and team performance. Studies have observed stress in the live operating theatre using a variety of methods , but limitations in ECG equipment and stress measurement methods have hindered research.…”
Section: Introductionmentioning
confidence: 99%
“…Our results can also be useful for the development of new generations of brain-computer interfaces able to control and enhance the human ability to make a decision in stressful situations. [42][43][44][45]…”
Section: Discussionmentioning
confidence: 99%
“…The TSST is comprised of a mock job interview in front of judges and a mental arithmetic task (serially subtracting 13 from 1022). The procedure has been described in detail elsewhere . The only difference between the current study and the previous one was that the preparation period was extended from 3 to 5 minutes in duration.…”
Section: Methodsmentioning
confidence: 99%